2D Ti3C2Tx MXene/polyvinylidene fluoride (PVDF) nanocomposites for attenuation of electromagnetic radiation with excellent heat dissipation. (February 2020) - Rajavel, Krishnamoorthy; Luo, Suibin; Wan, Yanjun; Yu, Xuecheng; Hu, Yougen; Zhu, Pengli; Sun, Rong; Wong, Chingping
Highlights: Assembly of novel 2D transition metal carbide (MXene) materials embedded with polyvinylidene fluoride (PVDF) as nanocomposites. MXene-PVDF nanocomposites explicated extraordinary conducting behavior largely preserved for superior attenuation of EMI energy. The enhanced thermal conductivity of fabricated MXene-PVDF nanocomposites relate with superior EM attenuation by dielectric components which would be dissipated as heat quickly. Abstract: The present study deals with novel, and cost-effective preparation of 2D MXene (Ti3 C2 Tx ) filled polyvinylidene fluoride (PVDF) polymer nanocomposite for the attenuation of electromagnetic interference (EMI). The obtained nanocomposite showed remarkable shielding effectiveness ( SE ) of 48.47 ± 3.5 dB for 22.55 vol% filler contents at a thickness of 2 mm. Formation of conducting network along with the assembly of micro capacitor network preserved for its high EMI shielding performance. The absorption dominated EMI shielding mechanism explained by the strong resonance, and interfacial polarization favors the loss of incident EM energy confirmed from dielectric measurements. Besides, the enhanced thermal conductivity of MXene-PVDF nanocomposites about 0.767 ± 0.034 Wm −1 K −1 at 22.55 vol% filler content depicts that a large amount of incident EM wave attenuated majorly by dielectric components which would be dissipated as heat quickly. The fabricated MXene-PVDF nanocomposites could be a potential candidate for EMI shielding materials and promising multifaceted electronic utilization.